Adoption of Enterprise Resource Planning and Organizational Performance. A Conceptual Study on Public Sector - Ibrahim Mohammed Massoud Egdair; M F Rajemi; Santhirasegaran Nadarajan (International Journal of Supply Chain Management, 2020)
Organizational Performance (OP) and the Enterprise Resource Planning system (ERP) are two of the most significant studies to provide benefits to the organizations. There are different investigations on the ERP and OP in private and public organizations in developed and developing countries. This paper basically review the relationship between ERP and OP. Notably, as only a few studies have addressed the implication of ERP on OP in Arab countries such as in the Libyan context, it needs more investigation. The main objective to review and explore to which extent the Libyan public organizations are looking to improve their performance through the ERP system